Cold Acclimation and Deacclimation of Two Garden Rose Cultivars Under Controlled Daylength and Temperature - Ouyang, Lin; Leus, Leen; De Keyser, Ellen; Van Labeke, Marie-Christine (Frontiers in Plant Science, 2020)
Low temperature stress is an important abiotic stress for garden roses in northern regions. Two garden rose cultivars (‘Dagmar Hastrup’ and ‘Chandos Beauty’) were selected to study the role of dehydrin and of carbohydrate metabolism during cold acclimation and deacclimation under the controlled daylength and temperature. The presence of bud dormancy was also observed as this could prevent budburst during warm spells. Both cultivars showed a similar changing pattern of cold acclimation and deacclimation and did not differ in their lowest LT50 values. Dehydrin (RhDHN5) was up-regulated by low temperatures and not by dehydration stress as the stem water content remained stable during the treatments. Total soluble sugars accumulated with a transient up-regulation of RhBAM3 (a key gene in starch hydrolysis) for ‘Dagmar Hastrup’ at 2 °C and a strong expression under both 2 °C and -3 °C for ‘Chandos Beauty’. At 2 °C and -3 °C, raffinose and stachyose strongly accumulated though the up-regulation of RhRS6 and RhGK differed in the cultivars. Although similar cold hardiness levels were reached, carbohydrate metabolism in response to cold stress is different in the two cultivars. Increasing the temperature after a cold period resulted in fast deacclimation as found by the downregulation of RhDHN5 and RhBAM3, the decrease of raffinose and stachyose. Bud endodormancy was hardly present in both cultivars.